Running training based on the law of linear momentum and its effect on developing certain specific phases of the 100-meter youth race - Al-Fadhli, Sarih; Abdul Karim Al-Madhkhouri, Hekmat (sports creativity, 2025)
Advanced sporting nations, which have won numerous Olympic medals in various sports, have turned to innovating methods and employing modern technologies to find alternatives to traditional training in order to achieve further development, break records, and enhance performance, particularly in athletics. Many mechanical laws related to body mass and speed, widely used in theory and employed by researchers as comparative variables, have been utilized to indicate the advancement or lag of these variables. The researchers then applied these variables, which are linked by the law of linear momentum (mass × speed), to determine the intensity of short-distance running training (in terms of both power and speed) for specific phases of a 100-meter sprint. This approach stems from their belief in the crucial role of mass in determining training intensity and the corresponding requirement for significant instantaneous force exerted at each push-off moment, which causes a change in the runner's speed. Therefore, the importance of the research came in using speed training and determining the intensity of the training in it through the law of linear momentum and according to the specific force and according to the variables of this law such as mass and speed, and monitoring these trainings and what happens to them in terms of changes in speed according to the amounts of force exerted using one of the modern technical devices to help in preparing the necessary trainings that enhance these factors according to the scientific foundations of a good plan to serve the training aspect and achieve achievement for one of the important age groups, namely the youth group, who are considered the basic basis for the development of achievement in the future.